(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Starting from the analysis of some emblematic stories, the Authors make clinical, ethical and legal considerations about the relationship of care and trust, especially regarding an appropriate advance care planning. The focus is on the communication and decision-making difficulties faced by healthcare professionals in dealing with the patient’s parents for the purpose of implementing the patient’s best interest. Prominent among the critical profiles highlighted are the role of the adolescent patient’s wishes, the definition of the quality-of-life standard pursued and the limits of appropriateness and usefulness of care, beyond which medical intervention is configured in the terms of futile medical care.